Hunting : Hunters, Game, Weapons, and Hunting Methods From the Remote Past to the Present Day - Brusewitz, Gunnar (London George Allen & Unwin Ltd., 1969)
Traces hunting as a vocation and sport from the earliest times in which man survived on the flesh of cave bears, mammoths, etc. to the present hunting of such animals little known to Americans as the ibex
Include Color Illustration and Index
Keywords: Game and game-birds -- Hunting